Short version of the Scale for Interpersonal Behavior: Slovak translation and psychometric analysis - Vráblová, Viktória; Halamová, Júlia (Frontiers in Psychology, 2022)
Assertiveness is a social communication skill and is related to the effectiveness of expressing oneself while respecting others. A lack of assertiveness is associated with various mental illnesses; hence the importance of being able to measure it reliably. The aim of the study was to translate the short version of the Scale for Interpersonal Behavior (s-SIB; Arrindell et al., 2002) into Slovak and subsequently test its factor structure and other psychometric properties. Our convenience sample consisted of 590 respondents from Slovakia, 22.71% of whom were men and 77.29% women. The data analysis consisted of a descriptive analysis, reliability analysis, factor structure analysis, reliability analysis, Mokken analysis, and percentile norms. The scale showed good psychometric properties. Unlike the 4-factor solution for distress and performance by Arrindell et al. (2002), our findings showed that the general factor loadings were very good and that the bifactor model had the best fit in both cases (distress and performance). The Mokken analysis indicateds that the total scores for distress and performance and their factorssubscales can be used. In line with Arrindell et al. (2002), Mokken analysis indicated that the total scores for distress and perfromance and their constituent subscales can be used as proposed. In conclusion, the Slovak version of the s-SIB can be used as to measure the total score for assertiveness as well as the separate subscales factors – Positive Assertion, Negative Assertion, Expression of and Dealing with Personal Limitations, and Initiating Assertiveness.